Few-photon SUPER: Quantum emitter inversion via two off-resonant photon modes - Quentin W. Richter; Jan M. Kaspari; Thomas K. Bracht; Leonid Yatsenko; Vollrath Martin Axt; Arno Rauschenbeutel; Doris E. Reiter (Physical Review Research)
With the realization of controlled quantum systems, exploring excitations beyond the resonant case opens new possibilities. We investigate an extended Jaynes-Cummings model in which two nondegenerate photon modes are coupled off resonantly to a quantum emitter. This allows us to identify few-photon scattering mechanisms that lead to a full inversion of the emitter while transferring off-resonant photons from one mode to another. This behavior is connected to recent measurements of a two-level emitter scattering two off-resonant photons simultaneously. Furthermore, our results can be understood as a quantized analog of the recently developed off-resonant quantum control scheme known as swing-up of quantum emitter (SUPER). Our intuitive formalism gives deeper insight into the interaction of a two-level emitter with off-resonant light modes with the prospect of novel photonic applications.